The Influence of a Tropical Climate with a Long Dry Season on Goat Semen Quality and Seminal Fluid Change in the Kanchanaburi Province, Thailand - S. Kimsakulvech; C. Nakthong; Y. Lanamtiang; T. Wongtawan (Faculty of Animal Science, Bogor Agricultural University, 2022)
At present, there is no information about the difference between the three seasons with a long dry period, such as Kanchanaburi province, Thailand, on goat semen quality. This study observed the climate and daytime length effects of a long dry period in three seasons in a tropical climate country on goat semen quality and seminal fluid change. The semen was collected from eight male goats once a month for one year. The libido score was assessed during semen collection. Semen volume, semen sediment volume, percentage of seminal fluid volume, seminal fluid protein, mass movement, motility, concentration, and spermatozoa membrane integrity were evaluated. Libido scores were not different between the seasons. Semen volume, seminal fluid volume, and seminal fluid protein concentration in the rainy season were significantly higher (p<0.05) than in the summer and winter. Semen sediment volume was relatively stable in all seasons and months. Meanwhile, the concentration was significantly higher (p<0.05) in the summer and winter than in the rainy season. In summer and winter, spermatozoa motility and normal spermatozoa membrane were significantly higher (p<0.05) than in the rainy season. In conclusion, temperature, THI, and daytime changes in tropical climate countries with long dry seasons were unrelated to semen quality, seminal fluid change, and sexual behavior. But the increase in humidity in the rainy season after long dry seasons has dropped semen quality, resulting from increased volume and protein levels in seminal fluid.